The Effect of Detergent, Temperature, and Lipid on the Oligomeric State of MscL Constructs: Insights from Mass Spectrometry. Issue 5 (21st May 2015) - Reading, Eamonn; Walton, Troy A.; Liko, Idlir; Marty, Michael T.; Laganowsky, Arthur; Rees, Douglas C.; Robinson, Carol V.
Summary: The mechanosensitive channel of large conductance (MscL) acts as an emergency release valve for osmotic shock of bacteria preventing cell lysis. The large pore size, essential for function, requires the formation of oligomers with tetramers, pentamers, or hexamers observed depending on the species and experimental approach. We applied non-denaturing (native) mass spectrometry to five different homologs of MscL to determine the oligomeric state under more than 50 different experimental conditions elucidating lipid binding and subunit stoichiometry. We found equilibrium between pentameric and tetrameric species, which can be altered by detergent, disrupted by binding specific lipids, and perturbed by increasing temperature (37°C). We also established the presence of lipopolysaccharide bound to MscL and other membrane proteins expressed in  Escherichia coli, revealing a potential source of heterogeneity. More generally, we highlight the use of mass spectrometry in probing membrane proteins under a variety of detergent-lipid environments relevant to structural biology. Graphical Abstract: Highlights: Mass spectrometry reveals different oligomeric forms of mechanosensitive channels Oligomeric state is exquisitely sensitive to temperature, detergent, and lipid MscL and other membrane proteins can bind to LPS when overexpressed in E. coli Abstract : Mechanosensitive channels act as emergency solute release valves, their oligomeric state being inherently linked with their function. Using mass spectrometry, Reading et al. explored the influence of construct, temperature, detergent, and lipid on the oligomeric diversity of this membrane complex.